(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Modular learning has emerged as a transformative approach within the modern education system, offering flexibility, personalization, and improved learner engagement. This article explores the conceptual framework of modular learning, its implementation in various educational contexts, and its impact on student performance and autonomy. Emphasizing a learner-centered design, modular learning allows students to progress at their own pace while acquiring competencies in segmented, manageable units. The paper also examines the benefits and challenges associated with modular learning, including its adaptability in remote and hybrid education settings. Through a review of current practices and empirical studies, this article highlights the critical role of modular learning in promoting inclusive, accessible, and efficient education in the 21st century.